2009
DOI: 10.1002/jmri.21691
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐contrast magnetic resonance quantification of normal pulmonary venous return

Abstract: Purpose:To assess the feasibility of phase-contrast magnetic resonance (PCMR) in quantifying the pulmonary venous return in normal subjects. Materials and Methods:PCMR was performed in 12 healthy adult volunteers (mean age 38 years, range 27-60 years; 9 men; body surface area 1.81 Ϯ 0.15 m 2 ) for the ascending and descending aorta, caval veins, main and branch pulmonary arteries, and pulmonary veins. Two readers independently quantified blood flow in all subjects.Results: Intraobserver differences were Ϫ2.0% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 19 publications
2
20
1
Order By: Relevance
“…12 In contrast, all patients in the current study showed a substantial amount of APC flow, with the minimum APC flow constituting 15.3% and 17.3% of the ascending aortic flow in BCPC and Fontan patients, respectively ( Table 2). …”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…12 In contrast, all patients in the current study showed a substantial amount of APC flow, with the minimum APC flow constituting 15.3% and 17.3% of the ascending aortic flow in BCPC and Fontan patients, respectively ( Table 2). …”
Section: Discussioncontrasting
confidence: 55%
“…8 -10 MRI is the gold standard for the quantification of arterial flow volumes, 10,11 and it has recently been shown that pulmonary venous flow volumes can be measured accurately using phase-contrast MRI. 12 We report the systematic use of MRI in the quantification of APC blood flow in patients after BCPC or modified Fontan procedure. We sought to investigate the risk factors for and hemodynamic consequences of these APCs.…”
Section: Editorial See P 171 Clinical Perspective On P 225mentioning
confidence: 99%
“…In our centre the intra-observer and inter-observer difference was 2% (95% CI) for blood flow through major vessels in the thorax. For systemic and pulmonary arterial and venous flow volumes the correlation coefficient range was 0.76–0.92 27. Direction and significance of changes from baseline were confirmed with corroborative flow measurements.…”
Section: Limitations Of the Studysupporting
confidence: 54%
“…In particular, it is unclear from the information provided in the study whether there was sufficient spatial resolution to minimize partial volume errors. 18 The authors reported better internal consistency when measuring pulmonary vein flow by MRI in a previous study, 19 in which the subjects were adults with normal anatomy. Additional validation work tailored to this clinical application is therefore warranted.…”
Section: Article See P 219mentioning
confidence: 90%